Review of marketing research. Vol. 10 - Malhotra, Naresh K. (Emerald, 2013)
Edited by Naresh K. Malhotra, this volume of Review of Marketing Research delivers a high powered range of articles from leading researchers and universities. The issue provides insights of interest to marketers throughout the discipline. Topics covered include a critical review on consumer experience and experimental marketing, designing and pricing digital content products/ services and nation equity. Authors include senior Chaired professors from such prestigious institutions as Wharton and Columbia. This volume adds to the already formidable body of knowledge built up by this highly respected book series.
Keywords: Business & Economics -- Marketing -- Research.; Sales & marketing management.; Marketing research.; elektronické knihy; electronic books